2021
DOI: 10.1016/j.psj.2020.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Study on the interactive effect of deoxynivalenol and Clostridium perfringens on the jejunal health of broiler chickens

Abstract: With global warming and ban on antibiotics, it occurs occasionally that deoxynivalenol ( DON ) together with Clostridium perfringens impairs the gut health of broiler chickens. However, the interactive effect of DON and C. perfringens on intestinal health is still unknown. A total of 120 one-day-old Arbor Acres broilers were randomly distributed to 4 groups. Birds were gavaged with C. perfringens (8 × 10 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
4
12
0
Order By: Relevance
“…A higher ratio of villus height to crypt depth has been linked to a greater capacity for nutrient absorption [ 45 , 46 ] whereas deeper crypts indicate faster cellular turnover in response to inflammation induced by pathogens or toxins [ 35 , 47 ]. In line with earlier studies [ 44 , 48 ], we found that C. perfringens challenge increased crypt depth but decreased villus height to crypt depth ratio, indicating compromised gut health. Furthermore, dietary encapsulated or powdered BP lowered crypt depth but increased villus height to crypt depth ratio compared with the challenged POS group.…”
Section: Discussionsupporting
confidence: 93%
“…A higher ratio of villus height to crypt depth has been linked to a greater capacity for nutrient absorption [ 45 , 46 ] whereas deeper crypts indicate faster cellular turnover in response to inflammation induced by pathogens or toxins [ 35 , 47 ]. In line with earlier studies [ 44 , 48 ], we found that C. perfringens challenge increased crypt depth but decreased villus height to crypt depth ratio, indicating compromised gut health. Furthermore, dietary encapsulated or powdered BP lowered crypt depth but increased villus height to crypt depth ratio compared with the challenged POS group.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous reports ( 68 , 69 ), the final body weight had a strong positive correlation with the ileal SCFAs (including total SCFAs, acetate, lactate, and butyrate), further indicating that the increased intestinal SCFAs levels were beneficial for ameliorating C. perfringens infection-induced compromise of broiler growth performance. Furthermore, the final body weight and ileal SCFAs (including total SCFAs, acetate, lactate, and butyrate) were positively correlated with SCFAs-producing bacteria ( Blautia, Oscillospira, Lactobacillus, Lactobacillus salivarius , and Butyricicoccus pullicaecorum ) and bacterial fatty acid biosynthesis, whereas negatively correlated with drug-resistant bacteria ( Bacteroides and Citrobacter ), which was partly consistent with previous findings ( 70 72 ). These results indicated that the body weight and intestinal SCFAs might be principal factors affecting the bacterial communities and microbial metabolic functions.…”
Section: Discussionsupporting
confidence: 91%
“…For TEM observation, after being fixed in 2.5% buffered glutaraldehyde, ileal segments were washed three times by a cold 100-mM phosphate buffer, and then postfixed in cold 0.1% buffered osmium tetroxide (OsO 4 ) for 2 h. After being washed by a phosphate buffer, the ileal segments were rapidly dehydrated in ascending grades of ethanol (30,50,70,95, and 100%), and then transferred into a 1:1 mixture of propylene oxide and epoxy araldite. The ultrathin ileal sections were embedded and cut by an LKB Nova ultramicrotome (Leica Microsystems, Buffalo Grove, IL) and then stained with uranyl acetate.…”
Section: Ileal Morphological Analysismentioning
confidence: 99%
“…In particular, DON elevated the expression of NF-κB, and FUM increased the expression levels of both NF-κΒ and TLR4 in the duodenum. In accordance with these findings, several studies have shown that dietary Fusarium mycotoxins included at concentrations close to EU limits upregulated TLRs [ 28 , 51 ] and pro-inflammatory and anti-inflammatory cytokines [ 5 , 6 , 28 , 51 ] in broiler proximal intestinal sites (duodenum and jejunum). However, in the study of [ 28 ], increasing the DON concentration up to 5 mg/kg of diet increased TLR and pro-inflammatory cytokine expression levels in the duodenum but downregulated them in the jejunum.…”
Section: Discussionsupporting
confidence: 60%
“…TJs include the peripheral membrane protein ZO-1, the transmembrane protein occludin (OCLN), and claudins (CLDNs) [ 22 ]. Moreover, mucin 2 (MUC2) is a crucial component of the intestinal mucosa layer, which covers its surface and repairs disruptions caused by factors such as xenobiotics and their metabolites [ 51 ]. As a result, downregulation of the expression of TJs and MUC2 might cause impairments to the intestinal barrier and hence reduce nutrient absorption [ 22 ].…”
Section: Discussionmentioning
confidence: 99%